Analisis Pengaruh Kepercayaan Merek, Pengalaman Merek, dan Ekuitas Merek Terhadap Loyalitas Merek Pada Vespa Matik di Surabaya - Erlinda, Sela Sefrina; Rachmat, Basuki; Widyantoro, Harry; Harsono, Soni (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
This research aims to analyze and identify the influence of brand trust, brand experience and brand equity on brand loyalty. The research was conducted on automatic Vespa consumers or customers with a total population of 115 people. The sample used was only 100 respondents because some samples did not match the criteria. Data collection techniques used were questionnaires via Google forms and conventional ones directly. Variable measurement uses a Likert scale with a scale of 1-7 and analysis for data processing uses the multiple linear regression method with the SPSS ver. 25. The research results show that brand trust and brand experience have a significant effect on brand loyalty, while brand equity has no effect on brand loyalty.